2012
DOI: 10.1002/term.549
|View full text |Cite
|
Sign up to set email alerts
|

Repair of surgically created diaphragmatic defect in rat with use of a crosslinked porous collagen scaffold

Abstract: Large defects in congenital diaphragmatic hernia are closed by patch repair, which is associated with a high complication risk and reherniation rate. New treatment modalities are warranted. We evaluated the feasibility of using an acellular biodegradable collagen bioscaffold for a regenerative medicine approach to close a surgically created diaphragmatic defect in a rat model. Scaffold degradation, cellular ingrowth and regeneration of the diaphragm were studied. In 25 rats, a subcostal incision was made and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…IGF1 may have diffused too rapidly and thus had a too short action period. In an earlier study we found that muscle regeneration is slow . More research on sustained growth factor release and dosage is recommended.…”
Section: Discussionmentioning
confidence: 93%
“…IGF1 may have diffused too rapidly and thus had a too short action period. In an earlier study we found that muscle regeneration is slow . More research on sustained growth factor release and dosage is recommended.…”
Section: Discussionmentioning
confidence: 93%
“…The use of porous collagen scaffolds has previously been shown feasible in a rat model for diaphragmatic hernia, 10 but muscle cell and blood vessel ingrowth were limited. Therefore, collagen scaffolds with heparin, HGF and VEGF were produced.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery was performed as described previously. 10 In short, a right-sided diaphragmatic defect of approximately 12 mm in diameter was created, and a scaffold was implanted with an overlap of scaffold with respect to the diaphragm at the abdominal side. Four non-absorbable interrupted sutures (Prolene 6-0) and 2-5 absorbable interrupted sutures (Vicryl 5-0, Ethicon) were used around the perimeter of the scaffold to close the defect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, modifications in pore size and orientation can further enhance tissue ingrowth (Brouwer, Daamen, van Lochem, et al, ). Previously, radial pore‐orientated collagen scaffolds implanted into the diaphragm of rats showed promising results (Brouwer, Daamen, Reijnen, et al, ), although a slower degrading material was suggested to be necessary for larger animal models (Brouwer et al, ). Few of these materials are extensively tested preclinically, and available models are often only partly representative.…”
Section: Introductionmentioning
confidence: 99%